Agricultural Biotechnology in Central and Eastern Europe: Determinants of Cultivation Bans. Issue 3 (10th April 2014) - Tosun, Jale
Abstract By the joining of the European Union (EU), the Central and Eastern European states had to align their agricultural biotechnology regulations to EU standards. In some cases, this meant the adoption of stricter regulations such as for the co‐existence of genetically modified organisms (GMOs) and conventional crops. In other cases, harmonisation with EU rules entailed the need to give up more restrictive national regulation, for example: to allow the cultivation of a limited number of GMOs. This article examines why some Central and Eastern European states joined the group of Western European countries that instituted bans on the commercial cultivation of GMOs in the EU. This study contributes to the literature in two ways. First, it contends that the prohibition of the commercial cultivation of GMOs in some Central and Eastern European member states must be interpreted in light of the EU‐wide public and political contestation of GMOs. Second, this piece of research shows that the ideological composition of governments matters in explaining the regulation of agricultural biotechnology. This second contribution allows for going beyond the predominant focus on public opinion when analysing the regulation of GMOs in the EU.